2015
DOI: 10.1016/j.chc.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Multisystemic Therapy for Externalizing Youth

Abstract: Synopsis Externalizing problems are multi-determined and related to individual, family, peer, school, and community risk factors. Multisystemic therapy (MST) was originally developed to address these risk factors among youth with serious conduct problems who were at-risk for out-of-home placement. Several decades of research has established MST as an evidence-based intervention for adolescents with serious clinical problems, including serious offending, delinquency, substance abuse, and parental physical abuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…MST is a family- and community-based intervention originally developed for juvenile offenders. More recently, it has been adapted for a range of serious externalizing problems, including violent offending and juvenile substance abuse (Zajac et al 2015). Because of the multidetermined nature of youth antisocial behaviors, MST targets concurrent risk factors at the level of the individual, family, school, and community.…”
Section: Treatment Of Aggressionmentioning
confidence: 99%
See 1 more Smart Citation
“…MST is a family- and community-based intervention originally developed for juvenile offenders. More recently, it has been adapted for a range of serious externalizing problems, including violent offending and juvenile substance abuse (Zajac et al 2015). Because of the multidetermined nature of youth antisocial behaviors, MST targets concurrent risk factors at the level of the individual, family, school, and community.…”
Section: Treatment Of Aggressionmentioning
confidence: 99%
“…Outcomes on externalizing behavior are reported, but not IA specifically. Currently, 11 randomized trials and eight studies in youths with CD support the efficacy of MST (Zajac et al 2015).…”
Section: Treatment Of Aggressionmentioning
confidence: 99%
“…As it stands, MST-SA is the version of MST that appears to best treat adolescent substance use problems. 38 A primary difference from other evidence-based treatments in that it is delivered in a time intensive manner leading to an average of 60 direct service hours per family over a 4 to 6 month period. 38…”
Section: Multi-systemic Therapymentioning
confidence: 99%
“…The program Multisystemic Therapy-Building Stronger Families (MST-BSF) is an adaptation of MST specifically for parents with substance use disorders (Schaeffer, Swenson, Tuerk, & Henggeler, 2013). The testing of this intervention is similarly ongoing (Zajac, Randall, & Swenson, 2015), however pilot results suggested that after mothers received this intervention, their youth had fewer anxiety symptoms, the mothers' drug use decreased, mothers had fewer depressive symptoms, and mothers were less likely to have additional substantiated cases of child maltreatment compared to parents who received comprehensive community treatment (Schaeffer et al, 2013). As testing continues for MST-BSF, ensuring that an adequate number of parents with OUD is included in trials will provide opportunities for comparison between parents with OUD and parents with other substance use disorders to understand whether the program effects are moderated by the type of drug use disorder a parent has.…”
Section: Oversampling Parents With Oud In Efficacy and Effectiveness mentioning
confidence: 99%